Manajemen Layanan Koperasi dan Kantin/Kafetaria di Sekolah Sekolah Menengah Pertama Negeri 02 Rambipuji - Ainun Ma’rifah; Khuriatus Salamah; Lusi Agustuti Handani; Qurotul A’yuni; Rofiq Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research describes cooperative exploration and canteen services at SMPN 02 Rampipuji. The importance of managing cooperative and canteen services in schools is increasingly being realized with changes in the consumption patterns of school residents. The aim of this research is to develop a more structured service plan that integrates cooperative and canteen principles into operational activities, which is expected to improve overall management. The research method used is a descriptive method with a qualitative approach. The population is all administrators and members of the cooperative and canteen of SMPN 02 Rampipuji, totaling 6 people. The research results highlight that cooperative and canteen managers have planned service development. However, to achieve this, it is necessary to improve the profit distribution system based on the activities carried out. The potential is to guide schools and cooperative and canteen managers in improving and enhancing the quality of their services. The findings show that although cooperatives and canteens operate, their management does not fully meet structured cooperative standards. The practical implications used in the research mean improvements to improve cooperative and canteen service standards according to appropriate cooperative and canteen SOPs.